The Influence Of Imagery Training On The Passing Ability Of Futsal Players, Islamic University 45 Bekasi - Azi Faiz Ridlo; Angga Prananda Bakti (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2021)
This study aims to examine the effect of imagery training on the passing ability of Futsal players at Islamic University 45 Bekasi. The method used in this research is the experimental method. Twenty Futsal players were given the task to attend and complete the Imagery training intervention for 5 weeks, 4 days / week. The instrument used in this study was the passing test. For data analysis using the t test. The findings of this study indicate that there is a significant effect of Imagery training on passing results, which is indicated by the calculation of the value of th (10,975)> tt (15) at α = 0.05 and dk = n-1, so that the null hypothesis (Ho) is rejected and it can be concluded that the imagery training method provides a significant increase in the passing results of the 45 Bekasi Islamic University Futsal Players. Then these findings also provide an imagery training model, especially for futsal.